2014
DOI: 10.1210/jc.2014-1087
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperglycemia Reduces Cerebrovascular Reactivity: The Role of Glycemic Variability

Abstract: GV is increased in patients with MS but without DM and is the major predictor of CVR reduction induced by acute hyperglycemia, possibly representing the earliest cause of cerebrovascular damage in DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Furthermore, patients with diabetes often overcorrect for hypoglycemia leading to "yo-yoing" of glucose levels and increased glycemic variability. The impact of glycemic variability on clinical outcomes remains unclear, although a growing body of literature has shown that increased glycemic variability is associated with adverse outcomes (5)(6)(7)(8), including increased rates of cerebrovascular events (9), white matter hyperintensities (10), and cognitive decline (11). However, the underlying mechanisms for these associations remain unclear.…”
mentioning
confidence: 99%
“…Furthermore, patients with diabetes often overcorrect for hypoglycemia leading to "yo-yoing" of glucose levels and increased glycemic variability. The impact of glycemic variability on clinical outcomes remains unclear, although a growing body of literature has shown that increased glycemic variability is associated with adverse outcomes (5)(6)(7)(8), including increased rates of cerebrovascular events (9), white matter hyperintensities (10), and cognitive decline (11). However, the underlying mechanisms for these associations remain unclear.…”
mentioning
confidence: 99%
“…Studies have found reduced CVR 18,19 or no differences between control individuals and those with MetS. 20 Although several studies have reported reduced resting cortical blood flow using ASL-MRI 21,22 or SPECT 23 methods, no studies have looked at CVR in obese insulin-resistant individuals without MetS or T2DM.…”
mentioning
confidence: 99%
“…Controversies exist about the effect of acute hyperglycemia, as mimicked by 2-3 h of 15 mmol z L 21 hyperglycemic clamp, on cerebral blood flow in healthy humans. This hyperglycemia either decreased resting cerebrovascular reactivity to CO 2 (29) or increased resting middle cerebral artery blood flow (30), whereas it did not alter middle cerebral artery blood flow during 10-min rhythmic handgrip exercise (31). Considering the latter results, the acute hyperglycemia, present only in a small proportion of the current patients, was probably not involved in the observed relative hypoperfusion in response to maximal exercise.…”
mentioning
confidence: 75%